2014
DOI: 10.1186/s40663-014-0015-2
|View full text |Cite
|
Sign up to set email alerts
|

A model of seasonal foliage dynamics of the subtropical mangrove species Rhizophora stylosa Griff. growing at the northern limit of its distribution

Abstract: Background: Progress of forest production in response to the environment requires a quantitative understanding of leaf area development. Therefore, it is necessary to investigate the dynamics of seasonal crown foliage in order to understand the productivity of mangroves, which play an important role in the subtropical and tropical coastlines of the world. Method: Crown foliage dynamics of the mangrove Rhizophora stylosa were studies to reveal patterns of leaf recruitment, survival and seasonal leaf area growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 60 publications
(64 reference statements)
1
4
0
Order By: Relevance
“…In general, evergreen mangrove species flash maximum leaves in summer and rainy season than those in winter (Leach and Burgin 1985;Reich et al 1991;Sharma et al 2014). R. stylosa flushed leaves 38.1% in summer of the annual total, whereas only 15.8% flushed in winter (Sharma et al 2014). Similar results were also reported by Kamruzzaman et al (2019) in Bruguiera sexangula, Allen and Duke (2006) in B. gymnorrhiza, Duke et al (1984) in Rhizophora apiculata, R. stylosa and B. gymnorrhiza.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In general, evergreen mangrove species flash maximum leaves in summer and rainy season than those in winter (Leach and Burgin 1985;Reich et al 1991;Sharma et al 2014). R. stylosa flushed leaves 38.1% in summer of the annual total, whereas only 15.8% flushed in winter (Sharma et al 2014). Similar results were also reported by Kamruzzaman et al (2019) in Bruguiera sexangula, Allen and Duke (2006) in B. gymnorrhiza, Duke et al (1984) in Rhizophora apiculata, R. stylosa and B. gymnorrhiza.…”
Section: Discussionsupporting
confidence: 77%
“…Leaf and stipule litterfall of this were maximum in summer and rainy season and minimum in dry season. Seasonal patterns of leaf recruitment are highly correlated with those of stipule litterfall (Sharma et al 2014). The balance between leaf fall and leaf gain is important in the maintenance of crown foliage dynamics, which regulate the primary productivity of the forests (Reich et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time to fully develop leaf anatomy and photosynthetic pigments depends on the species and the time of the year that leaves are born. Soto (1988), reported that new leaves of A. germinans reached their maximum size at between 4 to 6 months, whereas leaves from the genus Rhizophora reached their maximum mass, area and chlorophyll concentration in 3 to 4 months (Wang and Lin, 1999;Mehlig, 2001;Sharma et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Australia Coupland et al, 2005;Duke, 1990Borneo Sukardjo et al, 2013Brazil Mehlig, 2006Fernandes, 1999 India Upadhyay andMishra, 2010;Wafar et al, 1997Japan Kamruzzaman et al, 2016Sharma et al, 2014Kenya Slim et al, 1996Malaysia Hoque et al, 2015Akmar andJuliana, 2012 Mexico Agraz-Hernández et al, 2011;Utrera-López and Moreno-Casasola, 2008;Aké-Castillo et al, 2006;Arreola-Lizárraga et al, 2004;Day et al, 1987;Lopez-Portillo andEzcurra, 1985 Panama Cerón-Souza et al, 2014 South Africa Rajkaran and Adams, 2007 United States of America Castañeda-Moya et al, 2013…”
Section: Country Referencementioning
confidence: 99%